Hirschsprung disease and imperforate anus without fistula in a 5-year-old boy with Trisomy 21 - Paul R. Burchard; Suzanne N. Ramazani; Derek S. Wakeman; Marjorie J. Arca; Michael H. Livingston (Elsevier, 2021)
Background: Hirschsprung disease (HD) and anorectal malformations (ARM) occur in approximately 1 in 5000 live births. These conditions are associated with Trisomy 21 but their co-existence in a single patient is exceedingly rare. Case report: A male infant was born at 36 weeks gestational age with Trisomy 21 and imperforate anus without fistula. He underwent divided colostomy, posterior sagittal anorectoplasty, and colostomy reversal as three separate procedures. Two weeks after colostomy reversal, the patient developed abdominal distention and difficulty feeding. He underwent laparotomy, lysis of adhesions, and strictureplasty at the site of the previous colostomy reversal, but continued to struggle with abdominal distension and poor weight gain. Contrast enema and colonoscopy performed at 5 years of age revealed a patent anastomosis with significant dilatation of the colon proximal to the anastomosis and collapsed distal colon. Full-thickness biopsy of the neorectum was consistent with HD. The patient then underwent transverse colectomy, levelling colostomy, and mucus fistula creation. He recovered well with improvement in weight gain and abdominal distension. Conclusion: HD and ARM may co-exist in children with Trisomy 21 and other genetic syndromes. Rectal biopsy should be considered prior to colostomy reversal in patients with ARM and Trisomy 21.